2017
DOI: 10.1177/1356389017697615
|View full text |Cite
|
Sign up to set email alerts
|

Network-based approaches for evaluating ambient assisted living (AAL) technologies

Abstract: A network-based approach for evaluating ambient assisted living (AAL) technologies. Abstract.Ambient assisted living (AAL) technologies could support people experiencing physical or cognitive challenges, to and maintain social identities and complex activities of daily living.Although there has been substantial investment in developing AAL innovation, less effort has been devoted to understanding how to evaluate the impact of AAL on physical and mental health. Taking a theory-based evaluation approach, we sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…It is suggested that user-centred design could help and support the evolution of technology use in eldercare (Hakobyan et al 2013, Sánchez, Taylor, andBing-Jonsson 2017). Design that is based upon an understanding of older users, their tasks, and their environments and that is driven by user involvement is believed to more likely result in the use of technology that responds to the psychosocial and occupational needs of the users (Gomersall et al 2017), if the users are rightly involved (Joyce et al 2016). Lowhanging fruits are easily identified by user-centred design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that user-centred design could help and support the evolution of technology use in eldercare (Hakobyan et al 2013, Sánchez, Taylor, andBing-Jonsson 2017). Design that is based upon an understanding of older users, their tasks, and their environments and that is driven by user involvement is believed to more likely result in the use of technology that responds to the psychosocial and occupational needs of the users (Gomersall et al 2017), if the users are rightly involved (Joyce et al 2016). Lowhanging fruits are easily identified by user-centred design.…”
Section: Discussionmentioning
confidence: 99%
“…All of these are said to enable a safer, healthier, and more active lifestyle for older people, thereby maximising their independence, quality of life, and well-being (Milligan, Roberts, andMort 2011, Sánchez, Taylor, andBing-Jonsson 2017). It is suggested that monitoring and surveillance technologies (Peek et al 2014), as well as pendant alarms, smoke alarms, and fall detectors and sensors (Sánchez-Criado et al 2014, Bouwhuis, Meesters, and Sponselee 2012, Gomersall et al 2017) can be used to enhance safety, while it is suggested that information and communication technology (e.g. teleconferences, telecare, mobile phones, and portals) can improve social connectedness (Åkerberg, Söderlund, and Lindén 2017), and devices such as blood pressure meters, glucometers, and weighing scales can improve health and increase activity levels Moors 2015, Gherardi 2010) In Scandinavia, the term that is used-welfare technology-is a policy concept that was launched to promote digitalisation (Bygstad and Lanestedt 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of health technology research, a lively debate has developed concerning evaluation methods for the new generation of computer-assisted assistive technologies, such as telemedical systems and ambient assisted living devices, which are designed to support illness self-management in the home. Several authors have suggested that the randomised trial approach to evaluation is not fit for purpose to study the impact of these technologies (Gomersall et al, 2017;Greenhalgh, Procter, Wherton, Sugarhood, Hinder, & Rouncefield, 2015;Greenhalgh & Stones, 2010;Mortenson et al, 2015). Rather than treating technology as a simple bounded "intervention" whose effects can be neatly separated out from context and measured, these researchers have argued that health technologies are profoundly context-bound.…”
Section: Simple or Complex Complexity?mentioning
confidence: 99%
“…Rather than treating technology as a simple bounded "intervention" whose effects can be neatly separated out from context and measured, these researchers have argued that health technologies are profoundly context-bound. For instance, Gomersall et al, (2017) describe how their participants' technology use was largely determined by the social networks surrounding them. In a similar way, Greenhalgh and colleagues (2013) describe how the use and non-use of telecare was often dependent on the social systems in which the "users" were embedded: One participant never used his monitoring system because the couple he lived with were unable to assist him in sending his readings at the allotted time.…”
Section: Simple or Complex Complexity?mentioning
confidence: 99%
See 1 more Smart Citation